Demand Analysis on Forest-based Recreational Activities - Alessandro, Paletto; Claudio, Fagarazzi; Gianluca, Grilli; Leonardo, Lorenzini; Isabella, De Meo (Journal of Environmental Accounting and Management, 2026)
The nature-based recreational activities can be considered one of the most important cultural ecosystem services provided by forests. They provide benefits to local economy, human health and well-being reducing depression and mental illnesses risk and increasing social interactions. The aim of the present study is to assess the socio-economic importance of forest-based recreational activities using the travel cost demand analysis. The study was implemented in a black pine forest in Italy (Pratomagno forest) characterized by a multifunctional forest role and a diversified recreational attendance. The study on forest-based recreational activities was organized in four steps: development and pre-testing of a questionnaire; identification of the sample of visitors; administration of the questionnaire to the visitors; data processing. The results show that the most important forest-based recreational activity carried out by visitors is relaxing in the nature, followed by hiking and picnicking. The occasional visitors prefer more passive recreational activities (relaxing in the nature and picnicking), while regular and loyal visitors prefer more active recreational activities (hiking, mountain biking, picking non-wood forest products). A consumer surplus in the range between 39 and 44 \EUR\ per visit was estimated based on the model (Poisson and Negative binomial model), corresponding to 60.5-68.3~\EUR\ per hectare. The results show that nature-based recreational activities can generate positive direct and indirect benefits for forest managers and local people. The local decision makers should act on forest stand characteristics with the aim of increasing the recreational attractiveness and the consequent economic benefits.